Anti‐CD47 antibody suppresses tumour growth and augments the effect of chemotherapy treatment in hepatocellular carcinoma. (6th October 2015) - Lo, Jessica; Lau, Eunice Yuen Ting; So, Francis Tak Yuk; Lu, Ping; Chan, Vera Sau Fong; Cheung, Vincent Chi Ho; Ching, Rachel Hiu Ha; Cheng, Bowie Yik Ling; Ma, Mark Kin Fai; Ng, Irene Oi Lin; Lee, Terence Kin Wah
Abstract: Background & Aims: Hepatocellular carcinoma (HCC) is often associated with metastasis and recurrence leading to a poor prognosis. Therefore, development of novel treatment regimens is urgently needed to improve the survival of HCC patients. In this study, we aimed to investigate the in vitro and in vivo effects of anti‐CD47 antibody alone and in combination with chemotherapy in HCC. Methods: In this study, we examined the functional effects of anti‐CD47 antibody (B6H12) on cell proliferation, sphere formation, migration and invasion, chemosensitivity, macrophage‐mediated phagocytosis and tumourigenicity both in vitro and in vivo . The therapeutic efficacy of anti‐CD47 antibody alone or in combination with doxorubicin was examined in patient‐derived HCC xenograft. Results: Blocking CD47 with anti‐CD47 monoclonal antibody (B6H12) at 10 μg/ml could suppress self‐renewal, tumourigenicity and migration and invasion abilities of MHCC‐97L and Huh‐7 cells. Interestingly, anti‐CD47 antibody synergized the effect of HCC cells to chemotherapeutic drugs including doxorubicin and cisplatin. Blockade of CD47 by anti‐CD47 antibody induced macrophage‐mediated phagocytosis. Using a patient‐derived HCC xenograft mouse model, we found that anti‐CD47 antibody (400 μg/mouse) in combination with doxorubicin (2 mg/kg) exerted maximal effects on tumour suppression, as compared with doxorubicin and anti‐CD47 antibody alone. Conclusions: Anti‐CD47 antibody treatment could complement chemotherapy which may be a promising therapeutic strategy for the treatment of HCC patients.